Identification of explanatory variables pertaining to attack intensity on U.S. embassies in countries of the Middle East and North Africa. (June 2017) - Zoet, Zachary Alan
Abstract: This project examines the incidence of attacks on American Embassies located in the Middle East and North Africa. An attack intensity scale is developed based on a recent Department of State publication's description of attack events. Locational characteristics associated with attack intensity level are examined with multiple regression analysis. Identification of significant relationships between attack intensity and several explanatory variables produced a passing multivariate model that possessed a modest adjusted R Squared and a good R Squared value. The result indicates attack intensity correlated positively with tribalism, total literacy rate, GDP per capita and the number of mosques within range of the US Embassy. Negative correlations limiting the intensity of attacks include political stability, total dependency rate, refined oil exports, and life expectancy. The model's coefficients appeared stable because of minimal levels of multicollinearity present in the model. Highlights: A multiple regression analysis is used to study attacks on U.S. Embassies. A scale is developed to quantify attack intensity (dependent variable). The dependent variable is normally distributed. Eight explanatory variables are found from an initial dataset of approximately 50. categories of independent variables. A virtual globe Google Earth is presented as a platform for empirical research.